Analisis Sistem Pengendalian Internal Kas Pada PT. Sukses Transport Raya - Risna Nuraidah; Makhdalena Makhdalena; Fenny Trisnawati (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the effectiveness of the internal control system for cash management at PT Sukses Transport Raya, a company engaged in heavy equipment rental and scrap metal management in Pangkalan Kerinci, Riau. This research employs a qualitative approach with a case study method. Data were collected through interviews with three key informants, observation, and documentation, then analyzed using thematic analysis assisted by NVivo 15 software. The results show that the internal control system has been running quite effectively based on the five components of COSO 2013. The company has implemented a clear organizational structure with segregation of functions between large cash managed by the cashier and petty cash managed by each admin, a layered authorization system with the director as highest authority for expenditures above Rp10 million, computer-based recording, and monthly internal audits conducted routinely by the accounting department. However, several weaknesses were identified, including the absence of written standard operating procedures, reactive risk assessment without formal documentation, use of the site manager's personal bank account for field operations, and concentration of payroll responsibilities in one individual without adequate task segregation. It is concluded that the internal control system at PT Sukses Transport Raya has been sufficiently effective in preventing fraud, but still requires procedural formalization and strengthening of several COSO 2013 components to achieve optimal standards.